THE INTERACTION BETWEEN MESENCHYMAL STEM CELLS AND MACROPHAGES IN THE INFLAMMATORY MICROENVIRONMENT: Mesenchymal stem cells and macrophages in inflammation - Momčilović, Sanja; Kočović, Dušica; Milošević, Maja; Marković, Dragana; Vignjević Petrinović, Sanja (Srpski medicinski časopis Lekarske komore, 2025)
Mesenchymal stem cells (MSCs) are cells with significant therapeutic potential in regenerative medicine, primarily due to their capacity for self-renewal and differentiation into various cell types. The immunomodulatory properties of these cells enable them to regulate the inflammatory process, depending on their interaction with immune system cells. Macrophages, which are part of the innate immune system, can exhibit a pro-inflammatory M1 or an anti-inflammatory M2 phenotype, thereby influencing the immune response and tissue homeostasis. Mesenchymal stem cells affect macrophage polarization, thus modulating their effector functions. Conversely, macrophages can influence the differentiation potential of mesenchymal stem cells and their immunoregulatory function. The interaction between mesenchymal stem cells and macrophages, as well as their interaction with various immune and non-immune cells, highlights the complexity of processes within the inflammatory microenvironment. The interaction between these cells is essential for the tissue repair process. This brief review aims to analyze the importance of the interaction between mesenchymal stem cells and macrophages in certain inflammation-associated diseases, with special emphasis on the key role of the inflammatory microenvironment and the therapeutic potential of these cells.